Performance Analysis of the Protection and Control System of Cummins KTA19 Generator Under Operational Disturbances at 190 kVA Loading Conditions - Putra Rahmadi; Moranain Mungkin; Syarifah Muthia Putri; Indri Dayana (Sean Institute, 2026)
The 300 kVA Cummins KTA19-G3 generator set is equipped with an advanced electronic control system and protection system managed by the Engine Control Module (ECM), designed to maintain operational stability and prevent fatal damage due to abnormal conditions. This study aims to analyze the performance, response, and accuracy of both systems when the engine experiences disturbances in the form of rotation instability (hunting) and sudden stoppage (shutdown) at a load of 190 kVA (equivalent to 63.3% of maximum capacity). The methods used include measuring operating parameters, reading ECM data history using the Cummins Insite diagnostic tool, and analyzing the system's working logic. The results show that the speed control system (Electronic Governor) works as instructed but fails to stabilize the rotation due to physical obstacles in the fuel and air systems, causing a response delay of up to 1.2 seconds. In contrast, the protection system works very precisely and according to specifications, triggering engine shutdown when it detects rotation deviations exceeding the safe limit of ±6.6% and fuel pressure below the threshold of 1.0 Bar. It was concluded that the operational failure was not caused by damage to the electronic system, but rather by the limitations of the control system in dealing with mechanical disturbances, while the protection system functioned optimally as a last resort.